PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Fagry Maulana; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
This study was tested the influence of the firm characteristics to the Corporate social responsibility disclosure (CSRD) of insurance companies in Indonesia. The purpose of this research is to analyze the effect of company characteristics such as profitability, firm size, leverage and board of commisioners size on the corporate social responsibilitydisclosure on all insurance companies listed on the Indonesia Stock Exchange in 2009 until 2012. This research is an empirical study with purposive sampling techniques in data collection with the following criteria: 1. Insurance companies listed on the Indonesia Stock Exchange in 2009 until 2012. 2. Completed annual reports published in 2009 until 2012. The data obtained from annual report of Insurance companies listed on the Indonesia Stock Exchange. Data were analyzed bymultiple linear regressions to examine the influence of firm characteristics on the CSRD made by the firm.The hypothesis in this research is as follows, 1. Profitability of insurance company affect positively on the CSRD of the company, 2. Leverage of the insurance company affect negatively on the CSRD of the company, 3. Firm size affect positively on the CSRD of the company, 4. Board of commisioners size affect positively on the level of risk disclosure. The results from the test of hypothesis indicated that the firm’s size and company's board of commisioners’ size are significantly influenced on the CSR disclosure. Furthermore, leverage and profitabilityor the company does not significantly influence the level of CSR disclosure. The result of this study provides information for investor about the level of corporate social responsibility disclosure that company could have, and also useful to give information for decision making.